Development of genially interactive learning media for Indonesian language subject in elementary schools - Rahmad Setyo Jadmiko; Ria Fajrin Rizqy Ana (Jurnal Bidang Pendidikan Dasar, 2026)
Technological advancements in education require innovative learning media to enhance student engagement and motivation. Indonesian language learning in elementary schools still faces challenges due to the limited use of interactive media that support literacy development. This study aimed to develop Genially-assisted interactive learning media and evaluate its validity, practicality, and effectiveness. The research employed the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Validation by material and media experts indicated that the product was highly valid. Practicality testing showed positive responses from students (94%) and teachers (96%), categorizing the media as very practical. Effectiveness was demonstrated by improved students’ critical thinking skills, with an N-Gain score of 0.71 in the high category. Therefore, the developed media is considered valid, practical, and effective for supporting Indonesian language learning and enhancing critical thinking skills among elementary school students.